Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/jacs.9b09556
|View full text |Cite
|
Sign up to set email alerts
|

Inserting Nitrogen: An Effective Concept To Create Nonplanar and Stimuli-Responsive Perylene Bisimide Analogues

Abstract: Establishing design principles to create nonplanar π-conjugated molecules is crucial for the development of novel functional materials. Herein, we describe the synthesis and properties of dinaphtho­[1,8-bc:1′,8′-ef]­azepine bisimides (DNABIs). Their molecular design is conceptually based on the insertion of a nitrogen atom into a perylene bisimide core. We have synthesized several DNABI derivatives with a hydrogen atom, a primary alkyl group, or an aryl group on the central nitrogen atom. These DNABIs exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 109 publications
(120 reference statements)
1
31
0
Order By: Relevance
“…Our group has recently shown that inserting heteroatom(s) into a planar perylene bisimide (PBI) core is a promising approach to design non‐planar π‐systems with unique stimulus‐responsiveness (Figure 1). [7–9] For example, dinaphthoazepine bisimide (DNABI) 1 , a nitrogen‐inserted PBI derivative, underwent structural changes in response to the application of an external electric field, as the molecular motion of the asymmetric acceptor‐donor‐acceptor structure is associated with an orientational change of its dipole moment [7] . Dinaphthothiepine bisimide (DNTBI) S ‐oxide 2 underwent a sulfur‐extrusion reaction upon heating, which enabled the fabrication of an n‐type organic field‐effect transistor by a solution process [8] …”
Section: Figurementioning
confidence: 99%
“…Our group has recently shown that inserting heteroatom(s) into a planar perylene bisimide (PBI) core is a promising approach to design non‐planar π‐systems with unique stimulus‐responsiveness (Figure 1). [7–9] For example, dinaphthoazepine bisimide (DNABI) 1 , a nitrogen‐inserted PBI derivative, underwent structural changes in response to the application of an external electric field, as the molecular motion of the asymmetric acceptor‐donor‐acceptor structure is associated with an orientational change of its dipole moment [7] . Dinaphthothiepine bisimide (DNTBI) S ‐oxide 2 underwent a sulfur‐extrusion reaction upon heating, which enabled the fabrication of an n‐type organic field‐effect transistor by a solution process [8] …”
Section: Figurementioning
confidence: 99%
“…[29,30] Our group has recently become interested in the development of functional p-conjugated molecules by connecting naphthalene monoimide subunits with heteroatoms. [33][34][35] Herein, we report the synthesis and properties of acridino [2,1,9,8-klmna]acridine bisimides (AABIs) 5a-d (Figure 2b). AABI is an itrogen-doped anthanthrene derivative with two imide substituents.The structure of anthanthrene ( 6) is shown in Figure 2b.A cridino[2,1,9,8-klmna]acridine (7)i s ac lassical nitrogen-doped PA H, but its derivatization has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the synthesis of heteropines (7‐membered heterocycles featuring heteroelement) recently appeared as an appealing strategy [4] . For example various naphthyl‐fused heteropine incorporating oxygen A , [5] boron B , [6] nitrogen C [7] or phosphorus D [8] have been described in the last years (Scheme 1). All these π‐extended heteropines display a strongly distorted C‐framework and can be emissive in solution.…”
Section: Introductionmentioning
confidence: 99%